When must not is not forbidden - Szymański, Leszek (LingBaW. Linguistics Beyond and Within, 2023)
The present paper describes an empirical investigation into an English modal predicate with the auxiliary verb must, the negative particle not and the bare infinitive of the main verb. Typically, the negator not changes the meaning of must from obligation or strong recommendation to forbiddance. This, however, takes place only with the root flavor of must. Epistemic must does not interact with not in this way. The study uses authentic language samples retrieved from the online version of The Corpus of Contemporary American English. The analysis adapts the model of the semantic field of modal expressions developed by Kratzer (1991), and it attempts to find what lies behind the said lack of interaction between must and not. After a scrutiny of the conversational backgrounds influencing the studied modal meanings, the study found that the meaning expressed by a speaker with must not depends on whether the speaker evaluates the propositional circumstances directly or infers from them. Moreover, the study proposes patterns of must-not interfaces with regard to the modal flavor.